2021
DOI: 10.1126/sciadv.abi7166
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine receptor leak triggers fiber Ca 2+ redistribution to preserve force and elevate basal metabolism in skeletal muscle

Abstract: Muscle contraction depends on tightly regulated Ca 2+ release. Aberrant Ca 2+ leak through ryanodine receptor 1 (RyR1) on the sarcoplasmic reticulum (SR) membrane can lead to heatstroke and malignant hyperthermia (MH) susceptibility, as well as severe myopathy. However, the mechanism by which Ca 2+ leak drives these pathologies is unknown. Here, we investigate the effects of four mouse genotypes with increasingly severe RyR1 leak in skeletal muscle fibers. We find that RyR1 Ca 2+ leak initiates a cascade of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(105 citation statements)
references
References 63 publications
6
99
0
Order By: Relevance
“…(2017) for cardiomyocytes. The recent paper by Lamboley et al (2021) and coworkers has provided the first direct measurement of bound-to-free calcium ratio in mitochondria in FDB muscle fibers, the most used model of intact adult skeletal muscle fibers ex vivo. The total amount of calcium was measured by applying the lysis method, designed by Fryer and Stephenson (1996).…”
Section: Reggiani and Marcuccimentioning
confidence: 99%
“…(2017) for cardiomyocytes. The recent paper by Lamboley et al (2021) and coworkers has provided the first direct measurement of bound-to-free calcium ratio in mitochondria in FDB muscle fibers, the most used model of intact adult skeletal muscle fibers ex vivo. The total amount of calcium was measured by applying the lysis method, designed by Fryer and Stephenson (1996).…”
Section: Reggiani and Marcuccimentioning
confidence: 99%
“…For instance, as discussed (Section 3.1), a peak [Ca 2+ ] of 0.2-1 μM in mammalian fibres (Launikonis et al, 2009;Koenig et al, 2018) is untrue, and an inaccurate TT [Ca 2+ ] calibration was acknowledged when we compare papers in which estimated values of 100 μM (Launikonis et al, 2009) were updated to be over 1 mM (Cully et al, 2016). Another option, if all mentioned SOCE estimates turn true (then, ruling out any role in SR refilling or sarcoplasmic [Ca 2+ ] maintenance), and that the rate of exchange of Ca 2+ with the tubules is low (Lamboley et al, 2021), is that SOCE in skeletal muscle may be, under certain conditions, a custodian of the fibre total amount of Ca 2+ . Although complete models considering the internal equilibrium of Ca 2+ have already been presented (Section 3.1), models regarding its external equilibrium remain a pending task.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…The further characterization of these mouse models revealed that, in addition to inducing alterations in muscle contraction and/or structure, these RYR1 mutations can impact on other aspects of muscle biology that were not previously considered. For example, extracellular Ca 2+ entry was shown to be altered in some of these mouse models, and it was proposed that this may contribute, in the short or long term, to exacerbate muscle impairment ( Yang et al, 2007 ; Cherednichenko et al, 2008 ; Bannister et al, 2010 ; Estève et al, 2010 ; Eltit et al, 2013 ; Yarotskyy et al, 2013 ; Lamboley et al, 2021 ). In Ryr1 G2434R/WT and Ryr1 T4826I/WT mice, the decrease in SR Ca 2+ content due to channel leakage activates SOCE and increases mitochondrial Ca 2+ uptake ( Yang et al, 2007 ; Lamboley et al, 2021 ).…”
Section: Gain-of-function Mutations In Ryr1: In Vitro Characterizatio...mentioning
confidence: 99%
“…For example, extracellular Ca 2+ entry was shown to be altered in some of these mouse models, and it was proposed that this may contribute, in the short or long term, to exacerbate muscle impairment ( Yang et al, 2007 ; Cherednichenko et al, 2008 ; Bannister et al, 2010 ; Estève et al, 2010 ; Eltit et al, 2013 ; Yarotskyy et al, 2013 ; Lamboley et al, 2021 ). In Ryr1 G2434R/WT and Ryr1 T4826I/WT mice, the decrease in SR Ca 2+ content due to channel leakage activates SOCE and increases mitochondrial Ca 2+ uptake ( Yang et al, 2007 ; Lamboley et al, 2021 ). This is, initially, translated into activation of a preserving mechanism that leads to increased ATP production to support the greater demand of ATP exerted by SERCA pumps in their continuous activity to counteract Ca 2+ leak ( Lamboley et al, 2021 ).…”
Section: Gain-of-function Mutations In Ryr1: In Vitro Characterizatio...mentioning
confidence: 99%
See 1 more Smart Citation